An alternative approach for generating white light source - Hor, Chi Chong (2014)
Laser is a form of white light source and it is costly. The setup is complex. Therefore, there is a need to find an alternative approach to generate white light source which is cheaper than Supercontinuum and will be brighter than traditional lamps. There are different methods to obtain white light source such as using Oxyhydrogen Flame.